Pengembangan produk BUMDes Makmur Jetiskapuan melalui pengenalan potensi desa berbasis folklore - Andni, Riyan; Faza, Iqbal; Afandi, Johan (LPPM UNIVERSITAS DIAN NUSWANTORO, 2023)
Jetis Kapuan Village is a village in Undaan District, Kudus Regency which has a natural water resource called the pennant well. The lack of knowledge of the village government in developing the advantages of natural resources moved the team to provide assistance in developing natural resources with an approach based on the introduction of folklore so that historical products from cultural stories appear as the goal of excess air products in the hope of being able to penetrate market competition. This community service activity for Jetis Kapuan Village, Undaan District, took place on 28-30 September 2022 through a Focus Group Discussion (FGD) as the main activity event. The result of this community service activity is to provide knowledge to the community about the role of Village-Owned Enterprises (BUMDes) which seek to improve community welfare, besides that the community will better understand the principles in BUMDes management. In order for the village to become more advanced and developed, the community is more actively involved in BUMDes development efforts by understanding the village character and understanding the village program in the formation of BUMDes, if it continues to be carried out it will improve the welfare of the Jetis Kapuan village community.